Sex-based differences in immune function and responses to vaccination. (7th January 2015) - Klein, Sabra L.; Marriott, Ian; Fish, Eleanor N.
Abstract : Females typically develop higher antibody responses and experience more adverse reactions following vaccination than males. These differences are observed in response to diverse vaccines, including the bacillus Calmette-Guerin vaccine, the measles, mumps and rubella vaccine, the yellow fever virus vaccine and influenza vaccines. Sex differences in the responses to vaccines are observed across diverse age groups, ranging from infants to aged individuals. Biological as well as behavioral differences between the sexes are likely to contribute to differences in the outcome of vaccination between the sexes. Immunological, hormonal, genetic and microbiota differences between males and females may also affect the outcome of vaccination. Identifying ways to reduce adverse reactions in females and increase immune responses in males will be necessary to adequately protect both sexes against infectious diseases.